The Effect of Government Subsidies on Firm R&D Investment in China: From Perspectives of Ownership and Market Power - Haijing Wang; Junguo Shi; Muhammad Imran; Jiaqi Gao; Yitian Zhang; Rongyu Wang (Complexity)
This study examines the effects of government innovation subsidies under different combinations of market power (i.e., the relationship between enterprises, upstream suppliers, and downstream customers) and different types of ownership from the perspective of the contemporary marketing microenvironment. Based on the panel data of listed Chinese manufacturing companies from 2009 to 2018, the empirical results show that, in the case of higher buyer power, government subsidies will significantly promote the R&D investment of enterprises and the positive effect is not affected by nature of the enterprise’s ownership. In the case of lower buyer power and seller power, government subsidies significantly promote the R&D investment of nonstate-owned enterprises, but have no effect on state-owned enterprises. The conclusions of the study further verify that, under different combinations of market power, there are significant differences in the effects of innovation subsidies for enterprises with different forms of ownership, and these provide a theoretical point of reference for the government to implement innovation subsidies. This study not only fills the theoretical black box of the relationship between government subsidies and enterprise innovation but also provides relatively new empirical evidence for the related research on innovation subsidies in developing countries.